Lateropulsion After Hemispheric Stroke: A Form of Spatial Neglect Involving Graviception. (27th April 2021) - Dai, Shenhao; Piscicelli, Céline; Clarac, Emmanuelle; Baciu, Monica; Hommel, Marc; Pérennou, Dominic
Abstract : Objective: To test the hypothesis that lateropulsion is an entity expressing an impaired body orientation with respect to gravity in relation to a biased graviception and spatial neglect. Methods: Data from the DOBRAS cohort (ClinicalTrials.gov: NCT03203109) were collected 30 days after a first hemisphere stroke. Lateral body tilt, pushing, and resistance were assessed with the Scale for Contraversive Pushing. Results: Among 220 individuals, 72% were upright and 28% showed lateropulsion (tilters [14%] less severe than pushers [14%]). The 3 signs had very high factor loadings (>0.90) on a same dimension, demonstrating that lateropulsion was effectively an entity comprising body tilt (cardinal sign), pushing, and resistance. The factorial analyses also showed that lateropulsion was inseparable from the visual vertical (VV), a criterion referring to vertical orientation (graviception). Contralesional VV biases were frequent (44%), with a magnitude related to lateropulsion severity: upright −0.6° (−2.9; 2.4), tilters −2.9° (−7; 0.8), and pushers −12.3° (−15.4; −8.5). Ipsilesional VV biases were less frequent and milder ( p < 0.001). They did not deal with graviception, 84% being found in upright individuals. Multivariate, factorial, contingency, and prediction analyses congruently showed strong similarities between lateropulsion and spatial neglect, the latter encompassing the former. Conclusions: Lateropulsion (pusher syndrome) is a trinity constituted by body tilt, pushing, and resistance. It is a way to adjust the body orientation in the roll plane to a wrong reference of verticality. Referring to straight above, lateropulsion might correspond to a form of spatial neglect (referring to straight ahead), which would advocate for 3D maps in the human brain involving the internal model of verticality.